1979
DOI: 10.1002/1520-6629(197901)7:1<23::aid-jcop2290070105>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Halfway to where? A critique of research on psychiatric halfway houses

Abstract: Following a critical review of halfway house outcomes studies, the authors concluded that the effectiveness of halfway houses in facilitating the independent functioning of psychiatric clients in the community is open to question. It appears that because major deficiencies in the areas of autonomous atmospheres, employment training and community adjustment are often concealed by limitations in statistical indices of success. Further research is necessary before more definitive conclusions can be drawn related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The second question addressed in the evaluation of residential services is how a particular type of residential service works in different rehabilitation programs. A review of research on halfway houses (Cometa et al 1979) concluded that evidence on the effectiveness of this type of residence in reducing hospitalizations, improving economic self-sufficiency, reduc-ing symptoms, and promoting community integration was ambiguous at best. These findings lead to the conclusion that while community-based residential programs may be better than inpatient treatment, they do not necessarily lead to successful longterm community adjustment (Anthony and Blanch 1988;Carling et al 1988).…”
Section: Residential and Independent Livingmentioning
confidence: 99%
“…The second question addressed in the evaluation of residential services is how a particular type of residential service works in different rehabilitation programs. A review of research on halfway houses (Cometa et al 1979) concluded that evidence on the effectiveness of this type of residence in reducing hospitalizations, improving economic self-sufficiency, reduc-ing symptoms, and promoting community integration was ambiguous at best. These findings lead to the conclusion that while community-based residential programs may be better than inpatient treatment, they do not necessarily lead to successful longterm community adjustment (Anthony and Blanch 1988;Carling et al 1988).…”
Section: Residential and Independent Livingmentioning
confidence: 99%
“…Cometa and colleagues (Cometa, Morrison, & Ziskoven, 1979) examined halfway houses and found few programs that were directed toward vocational advancement or that encourage an autonomous existence. They also cited poor community adjustment by the residents, indicated by am-This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Residential Settingsmentioning
confidence: 99%
“…As a result of deinstitutionalization, many seriously mentally ill persons reside in a variety of community residential facilities. Unfortunately, the specific programmatic components that contribute to positive community adjustment remain unknown (Carpenter, 1978; Cometa, Morrison, & Ziskoven, 1979;Test & Stein, 1978b). Two residential characteristics were examined for their effect on social networks: facility type (X4) and individual resident's length of stay ( X S ) within a facility.…”
Section: Length Ofmentioning
confidence: 99%